KRISIS PAPUA DALAM PERNYATAAN PEJABAT NEGARA DI MEDIA ONLINE (Analisis Tekstual Konstruksi Wacana Kritis) - Roosinda, Fitria Widiyani (Masyarakat Indonesia, 2019)
Recently, Indonesia has undergone disintegration threat on Papua that has been started from incident that happened Papua college student dorm in Surabaya, and collision between Papua college student and local citizen in Malang, spread into chaos that happened in several Papua cities. And of course, national turmoil like this will create statement by many side, especially from government. This study analyse the statements by official in Indonesia related to Papua crisis that has been reported by online media. With Critical Discourse Analysis by van Dijk approach that divide discourse analysis into 3 dimension social practice context and the result is Indonesia online media difference just on schematic level.